PERAN ORANG TUA DALAM STIMULASI KEMAMPUAN BERJALAN ANAK USIA 0-1 TAHUN DI JALAN CANGKRING RT 20 RW 05 KABUPATEN BANYUASIN - Diana Ulpa Sari; Sri Sumanrni (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2021)
Every ability that a child acquires will definitely involve people in it. Parents have an important role in providing stimulation for children. The stimulation given by parents to children aged 0-1 years will be very beneficial for children in gaining the ability to walk. With the stimulation of the ability to walk children aged 0-1 years can prevent delays in walking children. The purpose of this study was to find out what stimulation was given by parents to children in helping children's walking ability. This study used descriptive qualitative method. The study was conducted on three research subjects who live on Jalan Cangkring RT 20 RW 05, Banyuasin Regency. Researchers used observation guidelines and interview guidelines in obtaining data. The data analysis technique in this study uses the Miles and Hubberman type of data analysis. The results of this study stated that child holden of parents in bacak or front of for ti-ta-ta, and then child holden in wald or door fence to start walk. And while to use tool walking ability are baby walker, chair and wheeled paralon.